Comprehensive integration of different transport services: case of non-metro cities - Sharma, Harshita (SPA Bhopal, 2021)
Integrated transportation system is a key enabler of smart transportation because it enables the provision of a seamless intracity, intercity and regional transportation experience. Integration of different transport services is one of the most important factors in increasing ridership and making public transportation investments more viable. On a global level, many big countries are spending significant amounts of money on integrating two or more modes, which would facilitate the last mile connectivity. Several academic studies were combined as case studies from different countries to include a body of literature on, how integrated transportation system’s impacts revenue? How does the integration system change according to the change in city size? In small cities, Integration is a subject of Intramodal, but as the city size increases integration changes along from Intramodal to Intermodal and then multimodal. An integration system is first created based on literature that is gathered from all kinds of relevant information. Attempts to develop an Integration model framework, based upon different city sizes and how it changes when a tier III city becomes tier II city and so on. We will be talking about two different cities of the same state to look for critical elements for implementing public transport integration. People perception and existing provision of services are a great deal of what such integrated public stations can do for the urban quality of life, for instance, ease of movement and being able to see one's destination. The city required a three-tiered structure (Physical, Information and Fare Integration) to effectively run the public transport integration in any city. These levels of integration also provide better convenience and seamless connectivity, providing surrounding context information, and obtaining stakeholders' active participation, and ensuring that stakeholders see how their quality of life is affected, which encourages users' investment in transit use. It is important because, every public transport is facing challenges due to the shifting of people from public transport to their private cars, which increase the demand for public transport. It is essential for customer ease, satisfaction because customers perceive public transport as attractive if they fulfil the needs and the following points. The research focuses on providing various solutions to an integrated public transit network as necessary for raising the standard of community transportation and growing the efficiency of public transport services.
Keywords: Transport services